Efektivitas Komunikasi Guru Bimbingan Konseling Di Sekolah Menengah Pertama Negeri 11 Mataram - Ni Luh Eka Yanti; Ni Putu Listiawati; Siti Zaenab (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2020)
The global situation makes life more competitive and opens opportunities for people to achieve a better status and level of life. The positive impact of global conditions has encouraged people to continue to think and improve abilities, while the negative impact of globalization is in the form of anxiety life, conflict, stressed, frustration, the tendency of disciplinary violations to the use of addictive substances. The negative impact of globalization also occurs in students of State Junior High School 11 of Mataram, some students show behavior dominated by disciplinary violations to juvenile delinquency, this is inversely proportional to character education promoted by the government and the vision of State Junior High School 11 of Mataram. To develop personality and behavior in school is certainly the main task of the teacher especially counseling teacher as a counselor. The strategy needed is through effective communication between counseling teachers and problematic students so that the similarity of meaning to behavior change in problem students is achieved. The purpose of this study was to (1) describe the form of effective communication between counseling teachers and problem students, (2) describe the communication effectiveness of counseling tutors, (3) capture the communication meaning of counseling teachers and problem students in Mataram 11 Junior High School. This research uses qualitative research methods. The basis of the theory used is the theory of symbolic interactionism, the communication theory of the SMCR model and nonverbal sign theory. Technique of collecting data in this research is method of observation, interview and documentation studies. Data analysis used is data reduction, data presentation and data verification. Data checking uses data triangulation techniques. The obtained results study are; (1) an effective form of communication between counseling tutors and problem students using interpersonal communication contained in individual service processes in the counseling process. (2) communication effectiveness shows that the process of delivering messages by counseling tutors acting as sources that convey messages in the form of personality ethics through channels or media to students as receive so that the similarity of meaning between counseling teachers reaches the purpose of the message conveyed in counseling process. (3) the meaning of communication in the counseling process is the meaning of a well-accepting counseling, meaning of a rejecting guidance and a dependent meaning and threating in the guidance process which is demonstrated through nonverbal behavior during the counseling process.